Cell therapy of heart pathologies - Lukash, L.L. (Інститут біохімії ім. О. В. Палладіна НАН України, 2008)
The review article is devoted to cellular cardiomyoplasty as a novel technology of treatment of cardiac insufficiency. The experiments on animals and the first clinical trials have shown the possibility to improve the contractile function of diseased heart after transplantation of different types of donor cells: ardiomyocytes, bone marrow enriched by hematopoietic stem cells and mesenchymal stem cells. The problems of cellular cardiomyoplasty are discussed.